Glioblastome Multiforme: A Bibliometric Analysis - Akmal, Manahil; Hasnain, Nimra; Rehan, Aiman; Iqbal, Unzela; Hashmi, Shariq; Fatima, Kaneez; Farooq, Muhammad Zain; Khosa, Faisal; Siddiqi, Javed; Khan, Mohammad K. (World neurosurgery, 2020)
Bibliometric analyses are widely used to gauge the scholarly impact of any scientific publication. We conducted a bibliometric analysis of the 100 most influential articles on glioblastoma multiforme (GBM). We searched Scopus using the keywords "Glioblastoma multiforme," "GBM," Glioblastoma," and "Grade IV glioma." A list of the top 100 articles was prepared. The articles were sorted according to the number of citations. A detailed analysis was carried out to identify the characteristics of the most influential studies. The 100 most cited articles in the field were published over 38 years between 1978 and 2018, with the maximum number of articles published in the 10-year period from 2001 to 2010. The total number of citations for 100 articles was 148,594 and 4.8% were self-citations. Citations ranged from 9624 to 617, with a median of 935 (interquartile range, 906). The top cited articles originated from 22 countries, with the greatest contributions from the United States. Nature made the greatest contribution to the research on GBM, with a total of 14 articles, and Cancer Cell and New England Journal of Medicine were the second biggest contributors. Fifty-seven studies focused on the pathogenesis of GBM. There were 12 authors who had ≥5 articles in the top 100 citation list. Only 31% of the articles were funded by public and private sector organizations. Our analysis highlights the characteristics of the most influential articles on GBM and provides valuable insight into the research that has been conducted in this field.